2018
DOI: 10.1007/s10637-018-0675-9
|View full text |Cite
|
Sign up to set email alerts
|

Survival outcome and prognostic model of patients with colorectal cancer on phase 1 trials

Abstract: Background: Patients with metastatic colorectal cancer (mCRC) who progress on standard therapies may be eligible for phase I trials. To better delineate the risk-benefit ratio, we assessed toxicities, clinical outcomes and prognostic factors. Methods: Records of mCRC patients on phase I trials at our institution over 18 years were reviewed. Univariable (UVA) and multivariable analyses (MVA) were undertaken and a prognostic model developed. Results: There were 187 enrollments on 37 phase I trials. Median age wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 32 publications
(43 reference statements)
0
5
0
Order By: Relevance
“…Recently, studies have reported different genetic models for predicting human cancer. [39][40][41][42][43] A weighted prognosis signature of six lncRNAs, including LINC01583, LINC00276, LU-NAR1, DKFZp434J0226, SFTA1P, and OGFOD3, was constructed for predicting CRC prognosis. However, the samples were only acquired from GSE datasets, and the number of samples was <100, which may not provide enough accuracy.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, studies have reported different genetic models for predicting human cancer. [39][40][41][42][43] A weighted prognosis signature of six lncRNAs, including LINC01583, LINC00276, LU-NAR1, DKFZp434J0226, SFTA1P, and OGFOD3, was constructed for predicting CRC prognosis. However, the samples were only acquired from GSE datasets, and the number of samples was <100, which may not provide enough accuracy.…”
Section: Discussionmentioning
confidence: 99%
“…To improve patient selection, several studies have established prognostic factors and scoring systems to better estimate OS. In all studies, multivariable analysis consistently identified lactate dehydrogenase (LDH), PS, albumin level, number of metastatic sites, platelet count, hemoglobin, lymphocyte count, and serum sodium as important prognostic variables …”
Section: Introductionmentioning
confidence: 95%
“…In all studies, multivariable analysis consistently identified lactate dehydrogenase (LDH), PS, albumin level, number of metastatic sites, platelet count, hemoglobin, lymphocyte count, and serum sodium as important prognostic variables. [5][6][7][8][11][12][13][14][15][16][17][18][19][20][21] There is a disconcerting disparity between the racial and ethnic distribution of patients undergoing cancer therapy and those enrolled in clinical trials. There is well-established literature that non-Hispanic White patients account for more than 90% of all cancer clinical trial accruals, [22][23][24][25] while constituting only 59.3% of the US population.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have classified the prominent clinicopathological factors into multiple categories based on their features [ 6 , 7 ]. Clinicopathological factors including the baseline characteristics, tumor burden, and tumor markers, which can be affected or associated with short- and long-term survival outcomes in colorectal cancer, are considered to be prognostic factors [ 8 , 9 , 10 ]. Baseline characteristics of patients with cancer include the age at which cancer was diagnosed, sex, and comorbidity status.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have particularly reported the effect of the patient’s baseline characteristics, tumor burden, and molecular markers on progressive disease in cancer [ 8 , 9 , 10 ]. However, the effect of baseline characteristics and tumor burden on the expression of tumor markers (such as vaspin) and progressive disease has seldom been discussed.…”
Section: Introductionmentioning
confidence: 99%